Preparation and Characterization of Activated Carbon from Lapsi (Choerospondias axillaris) Seed Stone by Chemical Activation with Potassium Hydroxide - Joshi, Sahira; Pokharel, Bhadra Prasad (Journal of the Institute of Engineering, 2014)
Activated carbon (AC) was prepared from Lapsi seed stone by chemical activation with Potassium hydroxide at 400°C. The AC was characterized by pH, moisture content, Fourier transform-infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), methylene blue (MB) and iodine (I2) number. FT-IR spectra indicated the presence of various oxygen containing functional groups on the surface of AC. SEM images show the highly porous characteristics of AC with full of cavities. The Iodine number of AC revealed that the AC was found to be highly micro-porous. The adsorption of methylene blue by prepared AC was analyzed by the Langmuir and Freundlich adsorption isotherms. The data fitted well to the Langmuir isotherm with monolayer adsorption capacity 158 mg/g. The analysis showed that the AC prepared from Lapsi seed stone activated with potassium hydroxide could be a low-cost adsorbent with favorable surface properties. DOI: http://dx.doi.org/10.3126/jie.v9i1.10673 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 79–88